All the young men : a memoir of love, AIDS, and chosen family in the American South - Burks, Ruth Coker; O'Leary, Kevin Carr (Grove Press, 2020)
"In 1986, twenty-six-year-old Ruth visits a friend at the hospital when she notices a door to one of the rooms is painted red. Nurses are drawing straws to see who will tend to the patient crying for his mother on the other side, all of them unwilling to help. Ruth immediately steps into the quarantined space herself, comforting the young man in his last moments. Before she realizes what she's done, word spreads in the community that Ruth is the only person willing to help these young men afflicted by AIDS, and is called upon to nurse them. Shuttling from patient to patient, Ruth forges deep friendships with the men she helps: Paul and Billy, Angel, Chip, Todd and Douglas, working tirelessly to find them housing and jobs, and burying their ashes in her own family's cemetery. She teaches sex-ed to drag queens after hours at secret bars and defies local pastors and nurses to help the men she cares for, ultimately advising then-Governor Bill Clinton on the national HIV-AIDS crisis and becoming a beacon of hope to an otherwise spurned group of ailing gay men on the fringes of an intensely conservative state. This moving and elegiac memoir honors the extraordinary life of Ruth Coker Burks and the beloved men with AIDS who fought valiantly for their lives during a most hostile and misinformed time in America"--